Implementasi Algoritma Dijkstra Menggunakan Adjacency Matrix - Ismawati, Iis; Maulani, Alfi (Jurnal Matematika, 2024)
Abstract: Dijkstra's algorithm is an algorithm that can support finding the fastest route by mapping alternative trajectories in finding travel routes. The aim of this research is to find alternative travel routes by implementing the Dijkstra Algorithm using the Adjacency Matrix to pick up goods from the PT Drop Center Warehouse. Cisoka Express Technology Jet. Survey data in the form of customer names and addresses from two sub-districts was used. The results obtained with the Dijkstra Algorithm using the adjacency matrix obtained 4 routes in searching for the shortest path to pick up goods in Cisoka sub-district with the first route totaling 5 points with a distance of 9.35 km, the second route totaling 5 points with a distance of 9 km, the third route totaling 3 points with a distance of 3.95 km and the fourth route consists of 2 points with a distance of 3.6 km. and for Solear sub-district there are 3 routes, the first route is 7 points 14.9 km away, the second route is 9 points 14.72 km away and the third route is 2 points 5.85 km away. . Keywords: Dijkstra's Algorithm, Matrix, Shortest Path